The preparation journey to B certification in a small service company: Achievements, challenges, and learnings from an action research - Fernando Oliani Vieira da Silva; Thomaz Wood Jr. (Regepe Entrepreneurship and Small Business Journal)
Objective of the study: To support the preparation journey of a small business for B Corporation certification while contributing to the body of knowledge on B certifications. Methodology: The study employed an action research approach, enabling close interaction with the analyzed company. Main results: The journey resulted in the submission of the B Impact Assessment (BIA) for the company´s B Corp certification. Formalizing corporate governance and implementing mechanisms to align socio-environmental objectives with business strategy were identified as critical success factors for the transition. Theoretical contributions: The study expands understanding of the transition process for small businesses toward sustainable business models, emphasizing the importance of governance practices and strategic alignment. It also identifies specific challenges faced by SMEs in pursuing B Corporation certification. Relevance: The research addresses a highly relevant topic in today’s context. It focuses on SMEs, a group often overlooked in sustainability discussions, despite representing a substantial portion of global economies. Contribution to management: The findings provide practical insights for SME managers. Formalizing governance and aligning socio-environmental objectives with business strategy are highlighted as fundamental practices for successfully transitioning to more sustainable business models.